The evolution of Home Economics as a subject in Irish primary and post-primary education from the 1800s to the twenty-first century. Issue 3 (3rd July 2019) - McCloat, Amanda; Caraher, Martin
Abstract: This paper is a historical review, documenting the evolution of Home Economics as a subject in Irish primary and post-primary education from the 1800s to the twenty-first century. In the 1800s and early twentieth-century domestic subjects, including cookery, was widely taught to females in both primary and post-primary schools. The philosophical underpinning of the subject was to enhance the quality of life for families. The subject remained a popular choice for young women up until the establishment of the Irish Free State which, thereafter, witnessed many changes in the teaching of cookery and domestic science in primary and post-primary schools. The core ideology of the subject has remained relevant and it aims to provide students with knowledge, practical skills, understanding and attitudes for everyday life as individuals and as family members. This reflects the richness of the subject from the past and the relevance of the subject in addressing issues of a twenty-first century society.